Progress with passivation and screen-printed metallization of Boron-doped monoPoly™ layers. (1st January 2022) - Padhamnath, Pradeep; Nampalli, Nitin; Khanna, Ankit; Nagarajan, Balaji; Aberle, Armin G.; Duttagupta, Shubham
Graphical abstract: Highlights: Passivation quality limited by the damage to the interfacial oxide layer. Sheet resistance limited by maximum solid solubility in polysilicon. Passivation deteriorates with increasing dopant density at the poly-Si– iO x interface. Metal contacts exhibit strong dependence on layer thickness and surface morphology. J0, pass ≈ 3.8 fA/cm 2 and J0, metal ≈ 98±4 fA/cm 2 achieved on planar surface. Abstract: In this work we have analyzed the doping, passivation and contact properties of boron-doped ( p + ) polysilicon (poly-Si) layers to understand the two key limiting factors for industrial adoption of p + poly-Si based passivated contacts: challenges with diffusion and challenges with screen-printed, fire-through (FT) metallization. Investigation of test samples with ex-situ doped poly-Si layers of varying thickness and surface morphologies revealed that sheet resistance ( Rsheet ) and passivation quality in ex-situ doped poly-Si are limited by the maximum solid solubility of boron in silicon, and possible damage to the interfacial silicon oxide ( iOx ) layer and increased Auger recombination at high diffusion temperatures, respectively. An interesting correlation is found between the maximum dopant density at the interface and the J0, pass, with the latter increasing with increasing dopant density. The contacts to p + poly-Si layers are formed with commercially available FT Ag/Al pastes by screen printing process. Metal contact properties strongly depend on the surface morphology and thickness of poly-Si layer. Lower contact resistivity was achieved on textured surface with thickest poly-Si layers, while lowest recombination under metal contacts was achieved with planar surface with thickest poly-Si layer. Further microstructure analysis of metallized interfaces using Scanning electron microscope shows partial etching of thick (220 nm) poly-Si layers and near complete etching of thin (20 nm) poly-Si layers by FT Ag-Al pastes. Using optimized doping and contact conditions, excellent surface passivation in unmetallized regions ( J0, pass of 3.8 fA/cm 2 ), contact resistivities as low as 1.2 ± 0.8 mΩ-cm 2 and recombination current densities under the metal contacts of 155 ± 10 fA/cm 2 are achieved on textured and planar samples respectively.